(untitled) (Journal of the College of Basic Education, 2022)
Man realized from time immemorial until now through collective communication, searching for indications Meanings and values ​​that paint a picture of the hero or heroism, as a characteristic that does not All the heroic nature, which are just the features that define the heroic symbol. His identity is defined by his being a symbol The group, on the other hand, considers it the face of the collision with the problems of its time. Because he has several attributes that qualify him because this post is taken. Among these features and characteristics that frame the concept of heroic meditation is The principle of challenging and conveying the impossible by force of will, and sometimes extraordinary performance.